Fat Embolization Syndrome Secondary to Steroid Treatment in a Case of Sickle Cell Vaso-Occlusive Crisis - Thirugnanasambandam, Ram Prakash; Maraikayar, Farish Mohamed; Liu, Marie; Elbashir, Khalid; Muthu, John (Case Reports in Hematology, 2023)
Fat embolization syndrome (FES) is often seen as a complication of fractures and has been known to cause respiratory failure, rashes of the skin, thrombocytopenia, and neurological damage. Nontraumatic FES is uncommon and occurs due to bone marrow necrosis. Vaso-occlusive crisis in sickle cell patients secondary to steroid therapy is a rare entity and not widely acknowledged. We report a case of FES secondary to steroid therapy administered for a patient with intractable migraine. FES is an uncommon yet serious complication that occurs due to bone marrow necrosis and is usually associated with increased mortality or damaging neurologic sequelae for the surviving patient. Our patient was initially admitted for intractable migraine and worked up to rule out any acute emergency conditions. She was then given steroids for her migraine which did not subside with the initial treatment. Her condition worsened, and she developed respiratory failure along with altered mental status requiring care in the intensive care unit (ICU). Imaging studies showed microhemorrhages throughout the cerebral hemispheres, brainstem, and cerebellum. The imaging of her lungs confirmed severe acute chest syndrome. The patient also had hepatocellular and renal injuries indicative of multiorgan failure. The patient was treated with a red cell exchange transfusion (RBCx) leading to an almost complete recovery in a few days. The patient, however, had residual neurological sequelae with the presence of numb chin syndrome (NCS). This report thus highlights the need to recognize potential multiorgan failure secondary to steroid treatment and the importance of initiating treatment with red cell exchange transfusions to decrease the risk of such complications secondary to steroids.